PERENCANAAN PEMBANGUNAN SPAL DAN IPAL UNTUK SARANA PENINGKATAN KUALITAS LINGKUNGAN DI INDUSTRI RAJUNGAN DESA BULU - Agum Wahyu Prasetya; Decky Rochmanto; Nor Hidayati (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2024)
Waste in the Rajungan Industry, Bulu Village, Jepara Regency cannot be managed properly because this industry does not yet have SPAL and IPAL. Liquid waste resulting from industrial processing is channeled directly into the sea, causing marine pollution. The planning objective of this final assignment is to determine the design of the SPAL and IPAL as well as the RAB needed in the planned SPAL and IPAL construction work in the Bulu Village crab industry. The results of this technical research show that the average amount of waste water produced during the processing process per day is 0.51 m3/day or 507.5 liters/day or 0.02 m3/hour. The appropriate processing system to be applied in the crab industry is using an anaerobic filter system with five processing units, namely oil and fat separation tank, equalization tank, initial settling tank, anaerobic filter and final settling tank. Based on the calculation of the total planning costs for SPAL and IPAL KUB. The Blessing of Samudra Rajungan Jepara in Bulu Village is IDR. 56,500,000.